Pengembangan e-modul fliphtml menggunakan media aplikasi cymath untuk meningkatkan kemampuan literasi matematika dan pengaruhnya terhadap antusiasme Mahasiwa dalam belajar materi aljabar - Hasanah, Nur; Ambarsari, Ida Fitriana; Astindari, Tri; Nuryami, Nuryami; Aisyah, Sitti (Academy of Education Journal, 2024)
This research is a development research that develops modules that are used as e-modules using fliphtml and inside the module is inserted cymath which is an application that can help solve linear algebra tasks. It is hoped that from this research students can improve their mathematical literacy skills and can have an interest in learning linear algebra. Mixed method research research that combines qualitative and quantitative research types. The validity of the e-module 4.5 is in the very valid category, the Student Worksheet 4.7 is in the very valid category and the learning achievement test 4.6 is in the very valid category and for the learning outcomes test it is not only tested through a validator but also tested for validity and statistical reliability and shows data valid and reliable. Practical is said to be practical from activity observer data in the teacher's criteria obtained a score of 3.8 and meets good criteria. Effectively it is said that practically from student activity analysis is in good criteria. % of students who gave a positive response. There is an influence on the enthusiasm of students who are taught using e-modufliphtml using the cymath application media